Atomic force microscopy methods and protocols - Santos, Nuno C. 1972-; Carvalho, Filomena ca. 20./21. Jh (Springer New York, 2019)
This book aims to provide examples of applications of atomic force microscopy (AFM) using biological samples, showing different methods for AFM sample preparation, data acquisition and processing, and avoiding technical problems. Divided into two sections, chapters guide readers through image artifacts, process and quantitatively analyze AFM images, lipid bilayers, image DNA-protein complexes, AFM cell topography, single-molecule force spectroscopy, single-molecule dynamic force spectroscopy, fluorescence methodologies, molecular recognition force spectroscopy, biomechanical characterization, AFM-based biosensor setup, and detail how to implement such an in vitro system, which can monitor cardiac electrophysiology, intracellular calcium dynamics, and single cell mechanics. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Atomic Force Microscopy: Methods and Protocols is useful for researchers at different stages, from newcomers to experienced users, interested in new AFM applications
1. Artifacts and practical issues in Atomic Force Microscopy -- 2. Quantitative analysis of structure and dynamics in AFM images of lipid membranes -- 3. Imaging artificial membranes using high-speed Atomic Force Microscopy -- 4. INVESTIGATING THE NANODOMAIN ORGANIZATION OF RHODOPSIN IN NATIVE MEMBRANES BY ATOMIC FORCE MICROSCOPY -- 5. Analysis of DNA-protein complexes by Atomic Force Microscopy Imaging: the case of TRF2-telomeric DNA wrapping -- 6. Cell topography and its quantitative imaging by AFM -- 7. Functionalization of AFM Tips and Supports for Molecular Recognition Force Spectroscopy and Recognition Imaging -- 8. Ligand-receptor binding on cell membrane: dynamic force spectroscopy applications -- 9. SINGLE-MOLECULE FORCE SPECTROSCOPY: EXPERIMENTS, ANALYSIS AND SIMULATIONS -- 10. AFM to study pore-forming proteins -- 11. Imaging and Manipulation of Extracellular Traps by Atomic Force Microscopy -- 12. Investigation of bacterial curli production and adhesion using AFM -- 13. Antimicrobial peptides: effect on bacterial cells -- 14. AFM Nanoindentation Experiments on Protein Shells: a Protocol -- 15. Structural and mechanical characterization of viruses with AFM -- 16. Quantification of the elastic properties of soft and sticky materials using AFM -- 17. Measuring the elastic properties of living cells -- 18. Measuring elastic properties of single cancer cells by AFM -- 19. Molecular recognition force spectroscopy for probing cell targeted nanoparticles in vitro -- 20. Biomechanical characterization of human pluripotent stem cell-derived cardiomyocytes by use of atomic force microscopy -- 21. Simultaneous AFM investigation of the single cardiomyocyte electro-chemo-mechanics during excitation-contraction coupling
Keywords: Microscopy